FAKTOR FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR KAKAO INDONESIA PERIODE 2006-2015 - Mohammad Arief Wibowo (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2017)
This research uses quantitative approach with stastistic model to examine factors influencingIndonesia Cocoa Export Volume based on annual data from Indonesia Cocoa Export Volume, Cocoa Domestic Price, Cocoa International Price, and Rupiah Exchange Rate to US in 2006 until 2015 The independent variables in this research are Domestic Cocoa Price, International Cocoa Price, and Rupiah Exchange Rate to US with dependent variable that is Indonesian Cocoa Export Volume. The data used is obtained from the officialwebsite of Indonesian Central Bureau of Statistics, Center for Agricultural Data and Information, and Directorate General of Estate Crops. This study refers to research that has been done previously in various countries including countries in Asia. Based on the results of empirical tests conducted shows that variables Domestic Cocoa Prices have a dominant influencein affecting Indonesia Cocoa Export Volume. The Indonesian Domestic Cocoa Price and the Rupiah Exchange Rate to US have a significantnegative effect on the Export Volume of Indonesian Cocoa.